1987
DOI: 10.1111/j.1365-2621.1987.tb05859.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heating Temperature and Muscle Type on Porcine Muscle Extracts as Determined by Reverse Phase High Performance Liquid Chromatography

Abstract: Samples from porcine longissimus muscles were heated to temperatures ranging from 4080°C to reach endpoint temperatures (0 min) or held at endpoint temperature for 30 min. Proteins in water-soluble extracts of these samples were separated and quantified by reverse phase high performance liquid chromatography (RP-HPLC). After heating to 60°C for 0 min or to 55°C and holding for 30 min, lactate dehydrogenase (LDH), pyruvate kinase (PK) and myoglobin appeared to comprise the bulk of the remaining soluble protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several methods have been developed for evaluating the endpoint temperature of cooked meat products. Protein denaturation has been shown to be an acceptable indicator of previous thermal treatment (Steele and Lambe, 1982;McCormick et al, 1987). The Food Safety and Inspection Service (FSIS) has suggested two methods, the coagulation test and acid phosphatase activity, to determine the endpoint temperature of meat products (USDA-FSIS, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed for evaluating the endpoint temperature of cooked meat products. Protein denaturation has been shown to be an acceptable indicator of previous thermal treatment (Steele and Lambe, 1982;McCormick et al, 1987). The Food Safety and Inspection Service (FSIS) has suggested two methods, the coagulation test and acid phosphatase activity, to determine the endpoint temperature of meat products (USDA-FSIS, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…LDH activity at 70.9 and 72.1 °C was not different (P > 0.05) and averaged 1.3 units/g of meat. Using revereed-phase high-performance liquid chromatography, McCormick et al (1987) also showed decreased LDH content in porcine muscle extracts between 65 and 70 °C.…”
Section: Resultsmentioning
confidence: 90%
“…Several sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) techniques have also been evaluated for assessing the end-point cooking temperatures of meat products (Steele and Lambe, 1982 al., 1974; Alvarez, 1990). The loss of protein solubility has been used to measure the degree of heat denaturation of muscle proteins extracted from heated muscle with water or low ionic strength salt solutions (Lee et al, 1974; Davis et al, 1987;McCormick et al, 1987). These methods are accurate but time-consuming and not practical for routine use.…”
Section: Introductionmentioning
confidence: 99%